2013
DOI: 10.1007/s10874-013-9256-7
|View full text |Cite
|
Sign up to set email alerts
|

Pleurozium schreberi as bioindicator of mercury pollution in heavily industrialized region

Abstract: This research is continuation of the investigation of metal accumulation in native and transplanted moss Pleurozium schreberi in the most industrialized and affected region in Poland (Upper Silesia). We tested the hypotheses that in Upper Silesia transplants of P. schreberi may be used in a 90 days bioindication experiment in case native specimens are absent; a 90 days exposure of transplanted P. schreberi was long enough for evaluation of Hg pollution of the environment. An assay was carried out with native m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Mosses are a useful tool in monitoring environment quality and identifying pollution sources [37]. The selected species has been used as bioindicator in active biomonitoring studies [38,39] and is capable of accumulating mainly copper and remove its ions from solutions [40,41]. Our biomonitoring (field) studies did not confirm large accumulation of this metal, however, this may be due to the fact that concentrations of heavy metals accumulated in mosses depended on the time and place of samples exposition [42].…”
Section: Resultsmentioning
confidence: 83%
“…Mosses are a useful tool in monitoring environment quality and identifying pollution sources [37]. The selected species has been used as bioindicator in active biomonitoring studies [38,39] and is capable of accumulating mainly copper and remove its ions from solutions [40,41]. Our biomonitoring (field) studies did not confirm large accumulation of this metal, however, this may be due to the fact that concentrations of heavy metals accumulated in mosses depended on the time and place of samples exposition [42].…”
Section: Resultsmentioning
confidence: 83%
“…Concentrations of the heavy metals Ni, Cu, Zn, Cd, Pb and Hg, accumulated by Pleurozium schreberi mosses samples differ from each other within and between study periods of a given year. The concentration of individual elements is influenced by the moss species used and their accumulation capacity, exposure time and other environmental factors (interactions among elements, temperature, humidity) [49][50][51]. The changes in concentrations between the two study periods are also due to the global lockdown situation caused by the coronavirus pandemic restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Samecka-cymerman. et al, (2010) [20] reported mean concentration of cadmium to the tune of 90µg/g. in Taxus baccata leaves from Poland.…”
Section: Cadmium (Cd)mentioning
confidence: 99%